The impact of waste handling on small-scale farming in Malawi - Braun, Sabina (2015)
This study assess the impact of human waste and household garbage on the concentrations of heavy metals in arable land on two sites located close either to a waste collecting point (WD) or waste water treatment plant (WWTP). Malawi suffers from poverty, low food security and problems with access to land. The aim was to find out if the assessed areas are contaminated with heavy metals and to evaluate the results and the land use in a historical, social and political context. Another objective is to evaluate the possible positive effects the waste can give in form of plant nutrients against the potential harmful effect that comes from heavy metal contamination. Soil and plant samples were collected from the three sites, and the concentration of Cd, Zn, Cu and Fe was measured with atomic absorption spectrophotometry (AAS) at the University of Malawi. After evaluation of the results, some samples were brought to Sweden for a second AAS-analysis for Cd, Pb and Cr. Unfortunately the results for Cd were considered unreliable and were therefore not used in the assessment. The concentration of metals in the soil was then compared with the general guideline values calculated by the Swedish Agency for Environmental Projection. In the comparison WD and WWTP both showed concentrations of Pb exceeding the general guideline value. The concentration of Pb found was much higher than expected, and the results need to be treated with care. The sites had both a higher soil concentration of N and P compared with a reference site. The study was limited by time constraints and hampered by broken equipment. However, the results can be used for planning a more detailed risk assessment of the areas. Future actions suggested in this study are: a more detailed risk assessment of metal pollution and hygienic aspects, updated information about background levels of metals in soil, control of Cd-content in imported fertilisers and an overall focus on ensuring access to agricultural land and input as well as secure places for depositing waste.